2020
DOI: 10.1021/acsanm.0c01702
|View full text |Cite
|
Sign up to set email alerts
|

Antimony- and Zinc-Doped Tin Oxide Shells Coated on Gold Nanoparticles and Gold–Silver Nanoshells Having Tunable Extinctions for Sensing and Photonic Applications

Abstract: This paper reports the synthesis and study of doped metal oxides as the shell in core−shell nanoparticle architectures. Specifically, the paper describes the synthesis of gold nanoparticles (Au NPs) and gold−silver nanoshells (GS-NSs) coated with antimony-and zinc-doped tin oxide (SnO 2 ) shells (i.e., Au@ATO, Au@ZTO, GS-NS@ATO, and GS-NS@ZTO) with a comparison to the undoped SnO 2 -coated analogues Au@SnO 2 and GS-NS@ SnO 2 . The doped tin oxide core−shell nanoparticles prepared here were thoroughly character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 71 publications
2
27
0
Order By: Relevance
“…The TEM images in Figure 5a and 5b shows the SnO 2 shell comprised of minute polycrystallites. This polycrystalline porous nature of the shell is consistent with SnO 2 synthesized using the sodium stannate method [23][24]27]. The TEM image in Figure 5a also confirmed that the formation of free SnO 2 nanoparticles was limited.…”
Section: Cur Res Mater Chemsupporting
confidence: 80%
See 3 more Smart Citations
“…The TEM images in Figure 5a and 5b shows the SnO 2 shell comprised of minute polycrystallites. This polycrystalline porous nature of the shell is consistent with SnO 2 synthesized using the sodium stannate method [23][24]27]. The TEM image in Figure 5a also confirmed that the formation of free SnO 2 nanoparticles was limited.…”
Section: Cur Res Mater Chemsupporting
confidence: 80%
“…After the successful synthesis of the TiO 2 NPs, tin oxide shells were grown around these nanoparticles, as outlined in Scheme 1. The synthesis strategy to grow the SnO 2 shells is loosely based on the method reported by Medhi et al [23]. The SnO 2 shells were formed by using an aqueous sodium stannate trihydrate precursor solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past few decades, the synthesis of single-component noble metal and metal oxide heterostructures has attracted great attention due to their unique size, shape, and composition-controlled properties and their applications in catalysis, sensors, and photonics. Recently, the combination of noble metals such as Au, Ag, and metal oxides, in particular Cu 2 O, in the form of core–shell nanomaterials has been reported. , Among the metals, Au has attracted greater attention due to its chemical stability and applications in various fields such as catalysis, sensors, and biomedical engineering. Au nanostructures with different shapes exhibit interesting optical and sensing properties, and particularly the morphology of gold nanocubes (AuNCs) is interesting because various other shapes can be prepared from the AuNC core. The pristine Au core shows good catalytic activity, which can further be enhanced by synthesizing core–shell NPs of Au as a core and metal oxide as a shell. The enhanced catalytic activity of core–shell nanostructures is observed due to the combination of metal and metal oxide .…”
Section: Introductionmentioning
confidence: 99%